A Single Center Randomized Controlled Trial Comparing Success Rates of Valsalva Versus Modified Valsalva Maneuver in Terminating Paroxysmal Supra-Ventricular Tachycardia - Zahoor, Sarmad; Khawaja, Muhammad Ali; Hashmi, Mubashar Sultan; Mahboob , Hafiz Mudabbar; Rana, Muhammad Asim; Sadiq , Zohaib (Indus Journal of Bioscience Research, 2025)
Background: Atrial tachyarrhythmia with PSVT is a frequent clinical phenomenon presenting as palpitation and can be life threatening at times. Vagal maneuvers are initial measures that can be employed to stop PSVT, of which the Valsalva maneuver is the most frequent. In a recent past, there have been modifications of these methods to improve the effectiveness of the methods. Objective: Hence, the objective of this study is to look at the efficacy of the traditional Valsalva maneuver compared to the modified Valsalva maneuver to stop PSVT in a single-center, randomized controlled trial. Methods: Altogether, 124 patients with diagnosed PSVT were randomized to either the Valsalva group or the modified Valsalva group. The first measure of efficacy was defined as the failure termination of PSVT within 2 minutes of beginning the maneuver. The secondary measures were therefore the degree of comfort of the patient, the rate of recurrence within 24 hours, and any side effects experienced. Categorical data were compared by chi-square tests, while continuous data were compared by t-tests. Results: The Modified Valsalva group resulted in a higher success rate of 68 percent in comparison with the traditional Valsalva group, which achieved only a 48 percent success rate (p=0.02). In particular, patients in the modified group achieved higher comfort (p = 0.03) and lower frequency of recurrence within 24 hours (p = 0.04). Side effects, if any, which were negligible, were not reported in either of the groups. Conclusion: The present study shows the effectiveness of the modified technique over the traditional Valsalva maneuver in the termination of PSVT, comfort to the patient, and reduced chances of recurrence. These results reinforce the use of such modified maneuvers in clinical procedures to enhance the many patients.